ANALISIS POSTUR KERJA TERHADAP KELUHAN MUSCULOSKELETAL DISORDERS (MSDs) PADA PEKERJA MEKANIK BENGKEL SEPEDA MOTOR X SEMARANG - Puspita, Dita; Suroto, Suroto; Kurniawan, Bina (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Each job has potential hazard and risk, both derived from work activities, tools and materials used, as well as the work environment. One of the dangers that may pose a health risk is the ergonomic dangers of Musculoskeletal Disorders (MSDs) complaints. MSDs are chronic disorders of the muscles, tendons and nerves caused by repetitive use, rapid movement, large power use, contact with pressure, awkward posture, low vibration and temperature. Motorcycle maintenance activities consist of six steps: measuring, disassembling, repairing, replacing with the new one or the repaired one, and adjusting. The purpose of this study is to analyze the work posture against musculoskeletal disorders (MSDs) complaints on mechanical workers of Semarang motorcycle workshop. The triangulation tool in this study is the result of an assessment of the Baseline Risk Identification of Ergonomic Factor (BRIEF) Survey. The type of research used is qualitative, while the research subject is contained 5 people with different motorcycle maintenance activities. All of the mechanical workers in the X motorcycle shop are men with the average working period of 5-12 years. The results shows that there are five different activities performed by mechanical workers of X motorcycle workshop with 45 work postures. Out of 45 work postures, there are 22 high-risk working postures (49%), 9 medium-risk working postures (51%), and 4 work-positions with mild risk (9%). The sickest part of the body is on the back, shoulders, and hands. The perceived complaints are pain, stiffness, and cramps. To avoid them, workers should conduct a stretching before the activity, on the sidelines during activity and after the move in order not to feel tired.